2021
DOI: 10.1186/s12877-021-02086-0
|View full text |Cite
|
Sign up to set email alerts
|

A change in temporal muscle thickness is correlated with past energy adequacy in bedridden older adults: a prospective cohort study

Abstract: Background Energy inadequacy has a great impact on health outcomes in older adult patients; however, it is difficult to evaluate energy adequacy in these patients, especially in home-care settings. We recently reported that temporal muscle thickness can be an indicator of nutritional status. The present study aims to examine whether a change in temporal muscle thickness is directly correlated with energy adequacy and, if so, to determine the cutoff value of a change in temporal muscle thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Four studies reported the association between TMT and SAH [ 9 , 21 , 23 , 24 ], two studies between TMT and ICH [ 25 , 26 ], and two studies between TMT and ischemic stroke [ 27 , 28 ]. The other four studies described the standard TMT values [ 18 , 29 ] and the relationship between TMT and nutritional status [ 19 , 20 ]. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 flow diagram [ 30 ] for systematic review is shown as Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies reported the association between TMT and SAH [ 9 , 21 , 23 , 24 ], two studies between TMT and ICH [ 25 , 26 ], and two studies between TMT and ischemic stroke [ 27 , 28 ]. The other four studies described the standard TMT values [ 18 , 29 ] and the relationship between TMT and nutritional status [ 19 , 20 ]. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 flow diagram [ 30 ] for systematic review is shown as Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Hasegawa et al also performed a prospective study [ 19 ]. The study aimed to examine whether a change in TMT evaluated by the ultrasonography was directly correlated with energy adequacy, and to determine the cut-off value of a change in TMT to detect energy inadequacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] Recently, temporal muscle thickness (TMT) obtained on cranial magnetic resonance images (MRI) has been introduced as a new surrogate marker with which to identify patients at risk of sarcopenia due to its high correlation with the skeletal muscle mass, muscle function and nutritional status. [12][13][14][15][16] These studies suggest that the estimation of skeletal muscle mass can be derived from assessing cranio-facial muscles including TMT directly from brain MRI scans 8 that are routinely obtained for glioblastoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hasegawa [19] 2021 48 TMT changes were directly correlated with energy adequacy in bedridden older adults.…”
Section: Author Year Number Of Cases Abstractmentioning
confidence: 97%